2017
DOI: 10.1016/j.biopsych.2016.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Immune Contributions to Cause and Effect in Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder that appears during the first 3 years of life and presents with a variable set of symptoms that include impairments in social communication, narrow and restricted interests, and repetitive behavior. ASD is the most rapidly increasing neurodevelopmental disorder and current estimates are alarming, indicating 1 in 68 children and 1 in 42 boys in the United States are on the spectrum (1). Despite this growing public health emergency, few effective tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Given the genetic correspondence between ASDs and ALTs, these results stress the importance to further investigate the relationship between immunogenetics and ASDs. Immune dysregulation, either in the form of ongoing inflammation or autoimmunity, is prevalent in ASDs (McAllister, 2017). ASDs are, in fact, associated with family history of autoimmune diseases, like celiac disease and rheumatoid arthritis (Atladóttir et al, 2009; Ludvigsson et al, 2013), and either increased or decreased levels of inflammatory markers have been found in the blood of ASD individuals (Goines & Ashwood, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Given the genetic correspondence between ASDs and ALTs, these results stress the importance to further investigate the relationship between immunogenetics and ASDs. Immune dysregulation, either in the form of ongoing inflammation or autoimmunity, is prevalent in ASDs (McAllister, 2017). ASDs are, in fact, associated with family history of autoimmune diseases, like celiac disease and rheumatoid arthritis (Atladóttir et al, 2009; Ludvigsson et al, 2013), and either increased or decreased levels of inflammatory markers have been found in the blood of ASD individuals (Goines & Ashwood, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The SCORE study ( n = 411) showed that the outcome of IVTA 1 mg groups is similar to IVTA 4 mg groups and can lower the rate of adverse events [131]. TA has numerous mechanisms of action, including anti-inflammatory effects, antiangiogenic properties and inhibition of VEGF, and other inflammatory cytokine expressions, such as IL-6, ICAM-1, and MCP-1 [132, 133]. Ozkiris et al evaluated the effect of TA injection on persistent CME in BRVO that failed to respond to previous laser photocoagulation.…”
Section: Treatmentmentioning
confidence: 99%
“…Since most inflammatory conditions are mediated by the immune system, such ASD patients as described above may have underlying immune-mediated inflammation, affecting both the brain and other organs. In fact, a role of immune-mediated inflammation has been implicated with the onset and progress of ASD by multiple researchers [ 5 , 6 ]. However, it has been difficult to elucidate how the immune system plays a role in ASD pathogenesis, since there are many immune abnormalities reported in ASD, affecting almost every arm of the immune system [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%